Analisis Pelaksanaan Strategi Positioning Pada Toko Roti Master Bread Perdagangan - Mutiah Khaira Sihotang; Ella Umayya (AGHNIYA : Jurnal Ekonomi Islam, 2021)
The purpose of this study was to determine the implementation of the positioning strategy at the Master Bread Perdagangan bakery. The research approach is a qualitative approach. The data sources come from primary and secondary data. The data collection technique is done by interviewing the managers and consumers of the Master Bread Perdagangan bakery. Based on the research conducted, the conclusion is that the positioning strategy has been implemented by the Master Bread Perdagangan bakery by providing a positive image, but there are obstacles, namely consumer doubt about the products being sold caused by consumers not liking certain products sold in stores and also store locations that are too sidelined so that they are often invisible or overlooked and have the same perception among similar companies. The positioning strategy is carried out by providing slogans to stores, providing the best service, and providing good quality at relatively low prices.